A cross-sectional study on patient satisfaction at International Islamic University Malaysia (IIUM) Family Health Clinic, Kuantan Pahang Malaysia - Che' Man, Mohamad; Yusof, Muhammad Zubir; Jamsaril, Amsyareezmi; Ameruddin, Amira Sofiyah; Khalid, Fakhri Syahmi; Che Alhadi, Shahidah (2021)
Primary care is the first level of care in the national healthcare system accessed by communities, whereby patient’s needs, preferences and expectations play an important part in their treatment plan. Therefore, it is important to identify the level of patient satisfaction